STUDENTS' PERSPECTIVES ON SATISFACTION WITH DISTANCE EDUCATION IN GHANA: A CLUSTER ANALYSIS - Mensah, Francis; Agyapong, Kingsley; Acheampong, Augustine (International Journal of Online and Distance Learning, 2021)
Purpose: The study sought to categorise students based on the preferences that influence their choice of distance education in Ghana. Methodology: Questionnaires were used to collect data from 120 students taking part in the UEW distance education programme at the Kumasi Girls SHS Study Center. Respondents were segmented into three clusters (highly, moderately, and least satisfied) based on four preferences (price, quality, packaging, and social boding) that influenced their satisfaction with the distance education programme. Result: Findings from both hierarchical and non-hierarchical cluster analysis with squared Euclidean distance and Ward's method showed that the highly satisfied cluster was driven by quality of service and the fees (i.e. price) of the UEW distance education programme. A further analysis of the differences between the clusters indicated that satisfaction with the UEW distance programme significantly differs across the three segments. Unique Contribution to theory and practice: UEW must take advantage of the significant impact of service quality and price factors on customer satisfaction that runs through all the segments to develop and implement strategic decisions in order to achieve a competitive advantage in the distance education market